Relationships Among Growth, Carcass Characteristics, and Myf5 Myf6, MyoD, and MyoG Genes Expression Level in Saanen Male Kids with Varying Slaughter Weights - Uğur Şen; Dilek Gökçek; Ömer Faruk Yılmaz; Hüseyin Mert Yüksel; Hasan Önder; Emre Şirin; Sibel Bozkurt; Sezen Ocak Yetişgin; Ceyhun Yücel; Karlygash Omarova; Thobela Louis Tyasi (Animals)
The objective of this study was to determine the relationship between the MRF gene family members and slaughter characteristics in Saanen kids with varying slaughter weights. Twenty male kids of the Turkish Saanen breed were individually fattened for 60 days after weaning under an intensive management system. The kids were divided into two groups: low slaughter weight (L; n = 11; ≤29 kg) and high slaughter weight (H; n = 13; >29) at the end of the fattening. After slaughter, muscle samples from Longissimus-dorsi (LD) and Semitendinosus (ST) muscles were obtained. Carcass characteristics were higher in H than in L kids (p < 0.05). Myogenic Factor 5 gene expression level in the LD muscle of H kids was higher (p < 0.05) than that of L kids. A similar trend was observed regarding Myogenic Factor 6 and Myoblast Determination Factor gene expression levels in the LD muscle (p < 0.05). Also, the Myogenin gene expression level of H kids was higher than that of L kids in both muscles (p < 0.05). There were positive correlations among the slaughter weight, carcass characteristics, and some MRF gene expression levels in both muscles (p < 0.05) that the higher gene expression increases the weight and affects the carcass characteristics. The study results suggest that the difference in slaughter weight at the end of fattening in Saanen kids may be due to the expression level of myogenic regulatory factor (MRF) genes. Fattening performance and MRF genes may have a positive correlation.